(untitled) (American Journal of Chemistry and Pharmacy, 2023)
5-Azacytidine is a hypomethylating agent that has for long been used in cancer therapy due to its ability to inhibit the protein DNA methyltransferase responsible for hyper-methylating DNA strands. Recently, studies involving in vitro, ex vivo, and in vivo experiments have assessed the cardioprotective effects of 5-Azacytidine during myocardial ischemia-reperfusion injury (IRI). However, the effect of this compound in restoring the damage induced to mitochondrial molecular machinery during IRI has not yet been explored. Understanding this would help us analyze the ways through which mito-targeted therapeutics can be used. The purpose of this study is to investigate the therapeutic impact of 5-Azacytidine, as DNA methylation is a very common epigenetic modification observed during IRI. Furthermore, the protective effect of the compound in alleviating the damage induced to mitochondria during IRI can be identified, as DNA methylation can leave a direct impact on the mitochondrial genes as well. An isolated mitochondria model will be used to determine the effects of 5-Azacydine on mitochondrial molecular machinery as the capacity to generate DNA, RNA, and proteins are preserved in isolated mitochondria. In this study, we focus on the mechanisms of mitochondrial replication, and translation to understand the effect of 5-Azacytidine on the IRI affected mitochondrial system. Mitochondrial dysfunction is also another key turn of events that happens during IRI. The role of 5-Azacyidine in preserving the functionality is also being assessed in our research. The findings of these experiments would help us determine the plasticity the compound imparts on mitochondrial molecular mechanism’s integrity and function post-induced IRI.